Carl Dawson and the Research Ideal: The Evolution of a Canadian Sociologist - Shore, Marlene (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1985)
AbstractCarl Dawson's development as a sociologist reflected a general trend in sociology's evolution out of theology and social work. Trained as a minister, Dawson rejected the religious vocation at some point after World War I to become a social scientist. Appointed to McGill in 1922, he strove to establish research as the foundation for understanding society, questioning the efficacy of social reform. His convictions stemmed from his Maritime Baptist background, wartime experience and education at the University of Chicago.In 1914, Dawson left the Maritime region where he had been born and raised to attend the divinity school of the University of Chicago. In so doing, he was following a well travelled route: poor economic conditions drove numerous people out of the Maritime provinces between 1910 and 1929, and the lack of doctoral programmes in Canada compelled many students to attend American graduate schools. With its strong reputation for research, the University of Chicago was a popular choice. Its divinity school, a Baptist stronghold, was attractive to adherents of that faith. That a number of its faculty members were Canadians also attested to the institutional ties that had long linked Baptists in Canada and the northern United States.In 1918, Dawson recessed from graduate studies for war service and resumed his studies in 1919 - his interests now sharply turned towards sociology. This shift was partly influenced by the Chicago divinity school's close ties with the sociology department - a result of the historic link between the social gospel and sociology generally - but was also the product of the school's position as a leader in liberal and radical theological doctrine. The modernists within the institution stressed that all studies of society, including religion, must accord with modern empirical methods. That, in addition to their acceptance of the ideas of John Dewey and the Chicago School regarding social development, led some to the conclusion that religion itself was but a form of group behaviour.In reflecting all those currents of thought, Dawson's Ph.D. thesis, "The Social Nature of Knowledge," hinted at the reasons for his departure from the ministry for a career in social science. Showing that all culture and knowledge, morals and ideals had social origins, Dawson concluded that even fact was not fixed truth but represented the decision of individuals to agree on certain points and issues. This explained why Dawson believed that research - a collection of facts - would aid in understanding society. The thesis was also marked by an opposition to social action, stemming from what Dawson had witnessed during the war and the upheaval which followed, but also, it must be argued, from the antiauthoritarian and antihierarchial strain in the Baptist faith. The fact that Dawson eschewed social action in much the same way as did Harold Innis, another Baptist educated at Chicago, suggests that there exists a tradition in the development of Canadian social science quite different from the one which Brian McKillop has traced in A Disciplined Intelligence, and it was that legacy which Dawson's brand of sociology represented.